Integrated analysis of genes encoding ATP‐dependent chromatin remodellers identifies CHD7 as a potential target for colorectal cancer therapy. Issue 7 (5th July 2022) - Zhang, Xingyan; Zhou, Yaoyao; Shi, Zhenyu; Liu, Zhenfeng; Chen, Hao; Wang, Xiaochen; Cheng, Yiming; Xi, Lishan; Li, Xuanyuan; Zhang, Chunze; Bao, Li; Xuan, Chenghao
Abstract: Background: Genes participating in chromatin organization and regulation are frequently mutated or dysregulated in cancers. ATP‐dependent chromatin remodelers (ATPCRs) play a key role in organizing genomic DNA within chromatin, therefore regulating gene expression. The oncogenic role of ATPCRs and the mechanism involved remains unclear. Methods: We analyzed the genomic and transcriptional aberrations of the genes encoding ATPCRs in The Cancer Genome Atlas (TCGA) cohort. A series of cellular experiments and mouse tumor‐bearing experiments were conducted to reveal the regulatory function of CHD7 on the growth of colorectal cancer cells. RNA‐seq and ATAC‐seq approaches together with ChIP assays were performed to elucidate the downstream targets and the molecular mechanisms. Results: Our data showed that many ATPCRs represented a high frequency of somatic copy number alterations, widespread somatic mutations, remarkable expression abnormalities, and significant correlation with overall survival, suggesting several somatic driver candidates including chromodomain helicase DNA‐binding protein 7 ( CHD7 ) in colorectal cancer. We experimentally demonstrated that CHD7 promotes the growth of colorectal cancer cells in vitro and in vivo. CHD7 can bind to the promoters of target genes to maintain chromatin accessibility and facilitate transcription. We found that CHD7 knockdown downregulates AK4 expression and activates AMPK phosphorylation, thereby promoting the phosphorylation and stability of p53 and leading to the inhibition of the colorectal cancer growth. Our muti‐omics analyses of ATPCRs across large‐scale cancer specimens identified potential therapeutic targets and our experimental studies revealed a novel CHD7‐AK4‐AMPK‐p53 axis that plays an oncogenic role in colorectal cancer. Abstract : Graphical Abstract: (1) The genomic analyses of ATPCRs across large‐scale cancer specimens identified potential therapeutic targets, including CHD7 in colorectal cancer. (2) CHD7 promotes chromatin accessibility and gene transcription in colorectal cancer cells. (3) Our study reveals a novel CHD7‐AK4‐AMPK‐p53 axis that plays an oncogenic role in colorectal cancer.